Upper Arm Exercises on Pain Intensity Among Patient with Breast Cancer Dharmais Cancer Hospital, Indonesia - Damayanti, Sri Utami; Nursanti, Irna; Irawati, Diana; Natashia, Dhea; Herawati, Eva (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aim: to determine the effectiveness of upper arm exercises on pain intensity among patients with breast cancer at the Dharmais Cancer Hospital, Indonesia. Methods: This study used a queasy experiment with pre-post-test and two-group design. Twenty respondents from breast cancer patients in each intervention and control group were recruited. The upper arm training intervention was carried out 3 times/week for 3 weeks. The Visual Analogue Scale (VAS) was used to assess pain, and linear regression and the dependent t-test with a significance level of 0.05 (CI 95%) were used for analysis. Result: The significant difference in pain levels between the intervention group and the control group shows that the mean difference in the pain level scale of respondents in the upper arm exercise intervention group was 2.50 (SD=0.60), while in the control group, the mean was 1.70 (SD=0.65). control group with (t=4.00, p=0.001), and age (p-value =0.023; OR=8.645) were predictors in this study. Conclusions: Upper arm exercises can be recommended to reduce pain in breast cancer sufferers, especially breast cancer patients who have undergone stage 1 and 2 mastectomy operations. It is recommended that further research involve respondents who had the same level of pain before upper arm exercises were carried out